Optimalisasi Pemanfaatan Limbah Home Industri Tempe Untuk Pakan Ternak - Kirei Qurrata'aini Qurrata'aini; Bowo Winarno; Anindya Mustiasani (CV. ITTC INDONESIA, 2026)
Tempe production at the home industry scale in Mayang Village, Gatak District, Sukoharjo Regency produces solid and liquid waste that has not been optimally utilized, thus potentially causing environmental pollution. Solid waste in the form of soybean pulp and husks still contains organic materials that can be processed into alternative livestock feed. Therefore, this community service activity aims to optimize the utilization of tempe waste while improving community knowledge and skills in waste management. The method used was a participatory descriptive approach through observation and waste identification, socialization on waste utilization, and training on producing fermented feed made from tempe pulp, bran, molasses, and EM4 with a seven-day fermentation period. The results showed that tempe waste is available in sufficient quantities and can be processed into more economical livestock feed, thereby reducing the potential for environmental pollution. This activity highlights the importance of productive and sustainable waste management at the community level.